Assessing Changes in Reaction Time Following RAMP Warm-Up and Short-Term Repeated Volleyball Specific Exercise in Young Players - Kacper Cieśluk; Dorota Sadowska; Justyna Krzepota (Sensors)
The assessment of the various skills of athletes is carried out in terms of their ability to perform sport-specific tasks. The cognitive abilities of the players have significance for their effectiveness. In volleyball, a player’s ability to react quickly appears to be crucial in responding to an opponent’s dynamic play. The aim of the study was to evaluate the changes in reaction time to light signals following warm-up and physical exercise. Eighteen volleyball players (15.58 ± 2.01 years) participated in the study. Four FITLIGHT TrainerTM discs were placed on the wall facing the participant to conduct the reaction time test. The participant’s task was to react as quickly as possible to the illuminated disc by touching it with the palm of their hand. The procedure was repeated five times: before the warm-up, after the warm-up, and after each of the three agility tests. Friedman’s ANOVA showed statistically significant differences in reaction time between the tests (Chi2 ANOVA = 61.23; p < 0.001). All tests performed after the warm-up according to the RAMP protocol showed statistically significantly better results than those before the warm-up (p ≤ 0.05). At the same time, no differences were observed between the tests performed after successive agility tests. The results indicated that a well-chosen warm-up plays an important role in shortening the time of visual-motor reaction to a light stimulus (RT). Subsequent studies should be expanded to include other research groups and assess other parameters.